Making a Difference One Night at a Time: An Annual Fundraiser for a Student-Run Free Clinic Raises Over 25,000 - Corbin, Alexandra F; Crossen, Patrick J; Pauly, Tyler; Hagerty, Jamie E; Kruger, Jessica S (Journal of Student-Run Clinics, 2024)
Introduction: The Lighthouse Free Medical Clinic (LFMC) is a student-run clinic (SRC) in Buffalo, NY, providing free healthcare to uninsured and underserved patients. The LFMC relies primarily on community fundraising events for financial support, with the Annual Winter Gala serving as its main source of funding. In February 2023, the Gala successfully raised over 25,000.00 in profit, surpassing previous records by adopting several new fundraising strategies. These funds will significantly exceed the clinic’s annual operating budget, enabling the expansion of patient services and the continued delivery of high-quality healthcare. Planning & Night of Gala: The student leaders of the LFMC meticulously planned the Gala, which involved soliciting donations from local businesses for basket raffles, organizing entertainment during the cocktail hour, and arranging a live auction featuring items donated by community members. Gala Impact: The 2023 Gala attracted 376 guests and generated a profit of 25,973.40. The event featured 47 basket raffles and 21 live auction donations. The resulting profit will be allocated to various expenses of the LFMC’s operations, including laboratory supplies, outsourced laboratory procedures, provider insurance policies, a food delivery initiative, patient transportation services, miscellaneous costs, and the expansion of future clinic initiatives. Conclusion: This descriptive report details the planning, implementation, and future directions of the Gala fundraising event. It serves as a valuable template for other SRCs across the nation, offering guidance on funding strategies to support their clinic operations.